A New Normal? Australian Responses to Terrorism and Their Impacts - Aly, Anne (Oxford University Press, 2013)
In the post 9/11 era much emphasis has been placed on the ‘new world’ in which the threat of terrorism is as certain as it is ever present. Public communication campaigns, increasing security measures and the ongoing ‘war on terror’ serve as salient reminders that terrorism has come to stay. Public fears of terrorism are fickle and easily influenced by terrorist events, media coverage of terrorism and political rhetoric. Yet these fears are much more complex than the fear of an unknown but impending doom. This Chapter explores the complexity of fears of terrorism through an examination of Australian responses to terrorism. Drawing on research into how Australians construct media and political images of terrorism, this Chapter argues that the fear of terrorism is more closely associated with the political and social responses to terrorism than to the threat of a terrorist attack per se. In an increasingly securitised culture, the fear of terrorism manifests in psychological responses that include an intensified quest for meaning; heightened patriotism nationalism; the suppression of dissent; and the acceptance of measures that would otherwise be considered extreme. Such responses elicit fear and contribute to the post 9/11 state of insecurity.